HUBUNGAN DUKUNGAN KELUARGA DENGAN TINGKAT KECEMASAN PADA ANAK USIA PRASEKOLAH YANG DI HOSPITALISASI DI RS SYECKH YUSUF GOWA - julianus ake (Jurnal Ilmiah Keperawatan dan Kebidanan Holistic Care, 2018)
ABSTRACT Objective: The purpose of this study was to determine the effect of warm compress on the decrease in body temperature in children who have febris in the nursery in RSUD. Spare Saladan Makassar. Methods: The design of the experiment was pre experimental with one group pretest post test desaign study design. Ie research that uses a group of subjects as well as performing measurements before and after treatment on the subject. The population is all children treated in the nursery of children aged 6-12 years old who care no longer than 3 days and amounted to 32 people. Result: Result of research obtained from 32 responden, 31 respondent experiencing decrease of body temperature where average body temperature of child before done compress that is 38.2130c and after done warm compress average body temperature become 38,110c.From result of data analysis by using statistic paired t test -test then obtained a significant result with value (p = 0,000) which means p value <? 0.05 then it can be concluded that that Ho rejected Ha accepted that there is influence of warm compress to body temperature in children who have febris in RSUD child care room. Spare Saladan Makassar. Discussion: Febris is a condition in which individuals experience or are at increased risk of constant body temperature above 37.80c. Conclusion: Should be from the results of this study as a source of scientific input and reference for discussion in improving science about warm compress in lowering the body temperature of febris children. Suggestion: The result of this research become input material for nurse to be used as nursing management in handling child with fever in RSUD. Salinity wedge Makassar and other health services